AN ANALYSIS THE TYPES OF ENGLISH USED BY THE SEVEN STUDENTS OF STKIP PARACENDEKIA NW SUMBAWA - Imam Syafei; Iwan Jazadi; Supriadin (GLOBAL: Education Language and Humanity Journal, 2023)
This study was conducted at STKIP Paracendekia NW Sumbawa, which entirely was executed at least 2 months. The participants of this study were the sixth semester students, the total number were 7 students, 5 females and 2 males. In collecting the data of this study, there were three relevance instruments that have been utilized, namely; questionnaire, pronunciation test, and interview. The findings of this study are; firstly, the sixth semester students of STKIP Paracendekia NW Sumbawa were more dominant used American English. Secondly, the sixth semester students of STKIP Paracendekia NW Sumbawa were still wrong in pronouncing the words, and the last, the sixth semester students of STKIP Paracendekia NW Sumbawa using American English caused they felt American is more easier than British English, and they are more familiar with American words.